5-alkyl-1, 3-oxazole derivatives of 6-amino-nicotinic acids as alkyl ester bioisosteres are antagonists of the P2Y12 receptor. (November 2013) - Bach, Peter; Boström, Jonas; Brickmann, Kay; Burgess, Laurence E; Clarke, David; Groneberg, Robert D; Harvey, Darren M; Laird, Ellen R; O'Sullivan, Michael; Zetterberg, Fredrik
Background: Recently, we reported ethyl nicotinates as antagonists of the P2Y12 receptor, which is an important target in antiplatelet therapies. A potential liability of these compounds was their generally high in vivo clearance due to ethyl ester hydrolysis.Results: Shape and electrostatic similarity matching was used to select five-membered heterocycles to replace the ethyl ester functionality. The 5-methyl and 5-ethyl-oxazole bioisosteres retained the sub-micromolar potency levels of the parent ethyl esters. Many oxazoles showed a higher CYP450 dependent microsomal metabolism than the corresponding ethyl esters. Structure activity relationship investigations supported by ab initio calculations suggested that a correctly positioned alkyl substituent and a strong hydrogen bond acceptor were necessary structural motifs for binding. In rat pharmacokinetics, the low clearance was retained upon replacement of an ethyl ester with a 5-ethyl-oxazole.Conclusion: The use of shape and electrostatic similarity led to the successful replacement of a metabolically labile ethyl ester functionality with 5-alkyl-oxazole bioisosteres.